Assessment of Sectoral Virtual Water Flows and Future Water Requirement in Agriculture Under SSP-RCP Scenarios: Reflections for Water Resources Management in Zhangye City - Wang, Yifei; Wu, Haowei; Li, Zhihui (Frontiers in Ecology and Evolution, 2022)
Water scarcity is a core issue that constraints the high-quality development of arid areas in northwestern China. Zhangye is an oasis city located in the Heihe River Basin in northwestern China. It is populated with an agriculture-dominated economy and faces more and more serious water crises. Virtual water is an indicator that can measure the embodied water in the traded products, which has been widely applied for making rational policies for water resources management. In addition, clarifying water requirements in agricultural sectors under future climate change scenarios is essential to develop more appropriate adaptation strategies. From this perspective, this study aims to evaluate and compare virtual water flows among various sectors in Zhangye for the years 2012 and 2017 with a single regional input-output model and to further clarify the future water requirement tendency in agriculture during 2020–2050 under different shared socioeconomic pathways and representative concentration pathways (SSP-RCP) scenarios. The results showed that the planting sector directly contributed most of the total water consumption with the highest direct coefficient of 3307.5 m3/yuan in 2012, whereas the manufacture of food products and tobacco processing sector had the largest proportion of indirect water consumption (99%) mainly from intermediate inputs of agricultural products. Water consumption intensity of all sectors on average decreased by 22% during 2012–2017, indicating an increasing water utilization efficiency in economic industries. Household consumption also can improve water utilization efficiency as the major pathway for final consumption (86.4% in 2017). Water scarcity in Zhangye was becoming increasingly prominent since virtual water net exports were higher than local consumption, especially in the agriculture, manufacturing, and energy supply industries. Moreover, under climate change scenarios, we found the highest level of water requirement per unit area occurred in 2000, but it still had an incremental potential by 2050, especially in SSP585. The high requirement intensity and large-scale maize planting caused a rising tendency of total crop water requirement with an annual increasing rate of 8.4% from 1980 to 2050. This makes it possible to adapt to climate change through scientific management measures and technical means. We further made policy implications for adaptive management of water resources in Zhangye.